Formasi Gas Buang Pada Pembakaran Fludized Bed Sekam Padi - Suprapta Winaya, I Nyoman; Gede Sujana, I Nyoman; Tenaya, I G N P (Jurnal Energi Dan Manufaktur; Vol 4, No.1 April 2010)
Fluidized Bed Combustion is the best technology for energy conversion of various fuel types such as biomass andwastes with low caloric content fuel. Biomass like rice husk has a great potentiality to develop as a fuel since the availability inIndonesia is abundant. This research aims to analyse gas emission from rice husk using fluidied bed combustion. Investigationwas conducted in a laboratory scale fluidized bed unit by varying operation temperature and gas fluidization. The results showthat emission gas of carbon monoxide and NOx at higher temperature of 600 0C was found lower compared to 500 0C at similarair velocity of 0.05 m/s.
Keywords: rice husk, emission gas, fluidization velocity, fluidized bed combustion.